Synthesizing Evidence on the Use of Virtual Reality and Augmented Reality in Medical Education and Health Care Practice: A Scoping Review - Rajesh Gouri; Punit Patel; Bhavikkumar Ishvarbhai Pateliya; Ashish Kharadi; Manish Nagendra; R. Pavani; Jyothi Vybhavi V S; Aniruddha Jibhkate; Jitendra Patel (Recent Updates in Disease and Health Research Vol. 3, 2024)
Augmented reality (AR) is a cutting-edge technology that merges digital three-dimensional representations with physical inputs. Accessible via portable devices, it provides an immersive setting for learning. Augmented reality has many potential uses in many fields, such as the arts, healthcare, retail, marketing, education, the military, tourism, travel, architecture, engineering, and manufacturing. Important in light of the COVID-19 epidemic and the trend towards online education, it excels in remote and interactive learning. The systematic review methodology used to source articles for inclusion in the study. The effects of AR on medical students’ experiences and learning are investigated in this study. Among the goals of AR-based learning that they cover is the need to simplify otherwise difficult concepts. Medical students’ knowledge, abilities, and social relationships may all be improved with the use of augmented reality, according to the experts. They shows certain augmented reality in medical training programmes such as HoloPatient, OculAR SIM, and HoloHuman. This Book chapter provides an insightful exploration of the application of Virtual Reality (VR) and Augmented Reality (AR) in healthcare.